BASIC TECHNIQUES SKILL OF VOLLEYBALL GAMES - Akhmad Sobarna; Sumbara Hambali; Henry Asmara; Sony Hasmarita; Idris Supriadi (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2023)
This research was conducted because the level of basic techniques skill of volleyball game students who did not know volleyball extracurricular at Saguling 1 Senior High School West Bandung was not yet known. The purpose of this study was to determine how much the level of basic techniques skills in volleyball game extracurricular volleyball students at Saguling 1 Senior High School West Bandung. This research is a quantitative descriptive study, the method used in this study is a survey method. The population used is the volleyball extracurricular students at amounting to 20 people. Data collection techniques using the top passing test using AAHPER face wall volleyball test, bottom passing test using the Brumbach forearms pass volleyball test, smash test using the stanley spike test, service accuracy test using the AAHPER serving accuracy test. The data analysis technique used was descriptive survey test. The results of the study can show that, as many as 3 students or (15%) are in the